Development of a Model for the Participation of Influential Groups in Municipal Policy Formulation - Malekshahi, Maysam; Rabiei Mondejin, Mohammad Reza; Givarian, Hasan; Momeni, Mandan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The primary objective of this research was to develop a model for the participation of influential groups in the formulation of municipal policies. Methodology: This study is developmental-applied in nature and descriptive-survey in terms of data collection method. Data were collected through field methods and interview tools. The sample population includes 10 professors, managers, and expert municipal consultants from Tehran and Alborz provinces, employing purposive sampling. Qualitative thematic analysis was utilized for data analysis. Findings: The research results indicated that the environmental system governing influential groups encompasses cultural, social, political, legal, and administrative dimensions, situational conditions, and the role of citizenship. Leverage points of participation, roles of stakeholder groups, and competencies, capabilities, and skills are identified as the core capabilities of influential groups. The processes of realizing the participation of influential groups also involve organizational capacities for participation, media platforms, strategies of influential group participation, and facilitation processes. Conclusion: The results and implications reflect the effective role-playing of influential groups and barriers to participation, including internal and external obstacles.